Improved protocol for plasma microRNA extraction and comparison of commercial kits - Sriram, Harshini (Array, 2021)
MicroRNAs are small, non-coding RNA molecules that are becoming popular biomarkers in several diseases. However, their low abundance in serum/plasma poses a challenge in exploiting their potential in clinics. Several commercial kits are available for rapid isolation of microRNA from plasma. However, reports guiding the selection of appropriate kits to study downstream assays are scarce. Hence, we compared four commercial kits to evaluate microRNA-extraction from plasma and provided a modified protocol that further improved the superior kit"s performance. We compared four kits (miRNeasy Serum/Plasma, miRNeasy Mini Kit from Qiagen; RNA-isolation, and Absolutely-RNA MicroRNA Kit from Agilent technologies) for quality and quantity of microRNA isolated, extraction efficiency, and cost-effectiveness. Bioanalyzer-based Agilent Small RNA kit was used to evaluate quality and quantity of microRNA. Extraction efficiency was evaluated by detection of four endogenous control microRNA using real-time-PCR. Further, we modified the manufacturer"s protocol for miRNeasy Serum/Plasma kit to improve yield. miRNeasy Serum/Plasma kit outperformed the other three kits in microRNA-quality (P <0.005) and yielded maximum microRNA-quantity. Recovery of endogenous control microRNA i.e. hsa-miR-24-3p, hsa-miR-191-5p, hsa-miR-423-5p and hsa-miR-484 was higher as well. Modification with the inclusion of a double elution step enhanced yield of microRNA extracted with miRNeasy Serum/Plasma kit significantly (P <0.001). We demonstrated that miRNeasy Serum/Plasma kit outperforms other kits and can be reliably used with a limited plasma quantity. We have provided a modified microRNA-extraction protocol with improved microRNA output for downstream analyses.